How family environment and child’s attitudes toward reading relate to Croatian children’s reading and writing skills in early schooling - Keresteš, Gordana (Array, 2011)
The aim of the study was to examine how family demographics, parental literacy activities with preschool children and children’s attitudes toward reading relate to Croatian children’s performance in reading and writing in second and third grade of primary school. Participants were 587 pupils from 7 primary schools, along with one of their parents taking part in an international study also aiming at investigating literacy skills in relation to working memory within different orthographic structures (English, Swedish, Estonian and Croatian). Hierarchical regression analyses revealed significant contribution of all studied predictors (demographic variables including child’s gender, mother’s education and number of family members ; parental literacy activities ; and child’s attitudes toward reading) to performance in reading and writing. However, relations between predictor variables and reading and writing scores differ for younger and older children. Proximal measures (parental literacy activities in preschool period and children’s attitudes toward reading) contributed more to children’s reading and writing in second grade, whereas distal, demographic variables (child’s gender and the number of family members) were more contributing in third grade. Mother’s educational level was an important predictor in both grades. Results suggested that both individual and family characteristics are important contributors to early reading and writing of Croatian children.